Monte Carlo transport of swift protons and light ions in water: The influence of excitation cross sections, relativistic effects, and Auger electron emission in w-values. (August 2021) - Tessaro, Verónica Belén; Gervais, Benoit; Poignant, Floriane; Beuve, Michael; Galassi, Mariel Elisa
Highlights: w -Values are a source of uncertainty in reference dosimetry for hadrontherapy. MDM-Ion is a Monte Carlo code developed for swift ions transport in liquid water. w -Values shown to be independent of both particle charge and energy. Electronic excitation and Auger electron emission strongly affect the results. w -Values in liquid water should be used as a benchmark for microdosimetry. Abstract: Purpose: To develop a particle transport code to compute w -values and stopping power of swift ions in liquid water and gases of interest for reference dosimetry in hadrontherapy. To analyze the relevance of inelastic and post-collisional processes considered. Methods: The Monte Carlo code MDM was extended to the case of swift ion impact on liquid water (MDM-Ion). Relativistic corrections in the inelastic cross sections and the post-collisional Auger emission were considered. The effects of introducing different electronic excitation cross sections were also studied. Results: The stopping power of swift ions on liquid water, calculated with MDM-Ion, are in excellent agreement with recommended data. The w- values show a strong dependence on the electronic excitation cross sections and on the Auger electron emission. Comparisons with other Monte Carlo codes show the relevance of both the processes considered and of the cross sections employed. W and w -values for swift electron, proton, and carbon ions calculated with the MDM and MDM-Ion codes are in very close agreement with each other and with the 20.8 eV experimental value. Conclusion: We found that w -values in liquid water are independent of ion charge and energy, as assumed in reference dosimetry for hadrontherapy from sparse experimental results for electron and ion impact on gases. Excitation cross sections and Auger emission included in Monte Carlo codes are critical in w -values calculations. The computation of this physical parameter should be used as a benchmark for micro-dosimetry investigations, to assess the reliability of the cross sections employed.